Identification of the somatosensory parietal ventral area and overlap of the somatosensory and auditory cortices in mice. (October 2015) - Nishimura, Masataka; Sawatari, Hiroyuki; Takemoto, Makoto; Song, Wen-Jie
Highlights: We delineated the somatosensory parietal ventral (PV) subfield in mice. PV responded most strongly to stimulation of distal body parts. Part of the auditory cortex overlapped with non-primary somatosensory areas. Auditory and somatosensory responses were non-additive in the overlapping area. Abstract: This study aimed to identify the parietal ventral (PV) area of the somatosensory cortex in mice and to determine whether auditory cortex and somatosensory cortex overlap. Using high resolution, voltage-sensitive dye-based imaging, we identified the PV area, which exhibited strong responses to stimulation of distal body parts but weak responses to stimulation of proximal and facial body parts. We further demonstrated a substantial overlap between the auditory and non-primary somatosensory areas, including the PV area. We found statistically significant non-additive integration of auditory and somatosensory inputs in the overlapping region, suggesting convergence of the two input streams at the cellular level. We have thus delineated the PV area in mice for the first time, and have shown that it is a likely site for the integration of auditory and somatic inputs.